Coniferains A and B, new eunicellin-based diterpenoids from the octocoral Cladiella conifera (Tixier-Durivault, 1943). (June 2022) - Zeng, Jhao-Syuan; Tseng, Chung-Chih; Tsai, Yu-Chi; Chen, Shun-Hua; Chen, Po-Jen; Chen, Nan-Fu; Wen, Zhi-Hong; Hwang, Tsong-Long; Sung, Ping-Jyun
Abstract: Two new eunicellin-based diterpenoids, coniferains A (1 ) and B (2 ), have been isolated from the soft coral Cladiella conifera . Structures of eunicellins 1 and 2 were elucidated by spectroscopic analysis and the structure of a known eunicellin, australin G, was revised. Graphical Abstract: ga1 Highlights: New eunicellin, coniferains A (1 ) and B (2 ), were obtained from an octocoral Cladiella conifera . The structure of a known eunicellin, australin G, was revised. Octocorallia belonging to genus Cladiella are proven to be rich sources of eunicellin-based diterpenoids.